How to Teach Terminology to ESP Students - Umida Ziyamukhamedova ; Holiskhon Mahksudova; Yoga Prihatin (Universitas Pancasakti Tegal, 2023)
Abstract. The internationalization of higher education brings particular changes to the learning process at universities. The most prominent of them is the increased use of English as a language of professional discourse. As students should use both their native language and a foreign one there is an essential problem of terminology interference. To solve the problem and to facilitate the professional communication and integration of students in global dimension it is necessary to carry out the work on terminology standardization. The most suitable form for such work is an information thesaurus.